REMOTE TEACHING AND INFLUENCES ON NATURE SCIENCE TEACHING - Henrique Ferreira Andrade, Luiz (Journal of Interdisciplinary Debates, 2022)
The year 2020 was marked by the emergence of the new coronavirus that, in Brazil, had a direct impact on the performance of teaching activities in teaching, bringing a reality that many students and teachers were still unaware of. Online classes in schools required rapid adaptation and improvisation, which led to the emergence of some adversities. This article elucidates this problem by bringing reflections on the unprecedented situation for all people working in education.